Dynamics of personal attitudes of inpatients with schizophrenia as a result of treatment with psychosocial interventions - A. V. Palin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2025)
Modern therapy of patients with schizophrenia spectrum disorders necessarily includes psychosocial interventions along with psychopharmacotherapy. The latter are being actively developed by specialists from different countries, and the effects achieved with their help are also widely studied. Both indicators characterizing the clinical state of patients and others are used as indicators of the effects of psychosocial interventions. Parameters of social functioning and changes in patients’ personal attitudes are often assessed.The article is devoted to evaluating the effectiveness of treatment programs using psychosocial interventions for patients with schizophrenic spectrum disorders at the inpatient stage of psychiatric care. Treatment using a specialized psychoeducational program was compared in terms of effects achieved with treatment where the method of psychosocial intervention was occupational therapy. A naturalistic open comparative prospective study design was used, with the use of psychometric reliable and valid assessment methods, and statistical analysis methods adequate to the obtained data (the Wilcoxon signed-rank test).The performed analysis allows us to assert the similarity of clinical condition in patients of the compared subgroups both before and after treatment with psychosocial interventions. The results indicate psychopharmacotherapy as the leading factor in achieving changes in the clinical picture of the condition at the inpatient stage of care for patients with schizophrenia spectrum disorders. At the same time, the nature of the program used has little influence on the clinical condition of patients.A different result was obtained when assessing the dynamics of patients’ psychological attitudes towards their disease and treatment. It was proven that patients of the main subgroup (who took part in treatment with the use of a specialized psychoeducational program) changed their ideas about their disease, its severity, main symptoms and ways of their control, increased confidence in the ability to control symptoms and the level of compliance with therapy. Also, patients in the main group achieved a significant reduction in selfstigmatization, reduced the level of experienced social distress, which reflects the restoration of their sense of self-worth, dignity, and self-esteem. Also, the patients of the main group had lower rates of social avoidance and social distress after the end of treatment than those of the comparison group. The study confirmed the greater effectiveness of inpatient treatment with the use of a psychoeducational program in comparison with an occupational therapy program for patients with schizophrenia spectrum disorders.